SARS-CoV-2 Infection in Pregnancy: Clinical Signs, Placental Pathology, and Neonatal Outcome—Implications for Clinical Care - Moresi, Sascia; Dell'Aquila, Marco; Salvi, Silvia; Rullo, Roberta; Fruci, Stefano; Stollagli, Francesca; Arena, Vincenzo; Lanzone, Antonio (Frontiers in Medicine, 2021)
Introduction: The current COVID-19 pandemic has been associated with high rates of mortality and with significant morbidity. Both the risk of infection for pregnant women and the risk of vertical transmission have been evaluated and the presence of SARS-CoV-2 virus has been demonstrated both in the placenta and in the amniochorionic membranes. However, the actual effects of this pathogen on pregnancy and on placental morphology are still unclear. Objective: To describe histopathologic findings in the placentas of women with SARS-CoV-2 infection during pregnancy and their correlation with clinical signs and perinatal outcome. Methods: Placental tissues from pregnant women with SARS-CoV-2 infection delivering between March 2020 and February 2021 were analyzed. Results: 106 placentas from women with SARS-CoV-2 infection during pregnancy who delivered in Fondazione Policlinico A. Gemelli were examined. Most of them were asymptomatic. All neonates had available test results for SARS-CoV-2 and only one resulted positive. Placentas tissues mainly showed signs of maternal vascular malperfusion and of placenta injury in terms of syncytial node increase (96.2 %), villar agglutination (77.3 %), neointimal hyperplasia (76.4 %), excessive fibrin deposition (43.3%), and chorangiosis (35.8%). No significant differences in the frequency of the histopathological lesions were observed according to maternal symptoms Conclusion: Looking to placental tissues from SARS-CoV-2 positive women at the screening performed close to delivery, placental injuries could be detected without any correlation with fetal and neonatal outcome. We hypothesize that short latency between SARS-CoV-2 infection and delivery is the main reason for these observations.